Bioavailability of nanoemulsified conjugated linoleic acid for an antiobesity effect - Kim D (Dove Medical Press, 2013)
Dongyeop Kim,1,3* Jin-Hong Park,2* Dae-Jun Kweon,2 Gi Dong Han11Department of Food Science and Technology, College of Natural Resources, Yeungnam University, Gyeongsan, Republic of Korea; 2BioHealth Convergence Center, Daegu Technopark, Daegu, Republic of Korea; 3Division of Applied Bioscience, Graduate School of Agriculture, Hokkaido University, Sapporo, Japan *These authors contributed equally to this workBackground: The aim of this study was to enhance the bioavailability of conjugated linoleic acid (CLA), which has low water solubility, using nanoemulsion technology and to evaluate the effects of its improved bioavailability as an antiobesity agent.Methods: The antiobesity effect of nanoemulsified water-soluble conjugated linoleic acid (N-CLA) was evaluated using in vitro and in vivo studies. Differentiated 3T3-L1 adipocytes were treated with CLA and N-CLA to assess their lipolytic effect. Further, to confirm the antiobesity effect of N-CLA, male Sprague-Dawley rats were randomly separated into four groups, ie, a group fed a normal diet, a group fed a high-fat diet (obesity rat model), a CLA-treated group, and an N-CLA-treated group.Results: N-CLA showed a greater lipolytic effect on differentiated 3T3-L1 adipocytes compared with normal CLA. N-CLA enhanced the release of glycerol from triglycerides, which accumulated in differentiated 3T3-L1 adipocytes. Further, N-CLA enhanced leptin secretion to an extent similar to that of orlistat, an antiobesity agent. In an animal obesity model fed a high-fat diet, N-CLA attenuated accumulation of triglycerides, total cholesterol, and low-density lipoprotein cholesterol in serum, and also significantly decreased the volume of triglycerides and cholesterol in liver tissue.Conclusion: These results indicate that N-CLA has a greater antiobesity effect than CLA as a result of its improved bioavailability.Keywords: conjugated linoleic acid, nanoemulsion, water-soluble, improved bioavailability, antiobesity